A Transmission Mechanism of Self-Adjustment Pipeline Oriented on Common Content Characteristics - Peng,ZhangZhen Yi; Dongnian Cheng; Julong Lan (Dianxin kexue)
Content-centric networking is the core of future network. Current network was established on the inter-connection of host, in which the bottom transmission units could not denote semantics of upper content. The content characteristics for various applications were concluded. The network transmission structure which was named parametric self-adapting content pipeline for content characteristics was consturcted. The mapping between content characteristics and the pipeline was established. All content characteristics would be normalized by pipeline parameters, and therefore establish the self-adapting transmission channel driven by content characteristics. In detail, the resolution of content characteristics, the structure of content pipeline,the automatic matching between pipeline and content characteristics were researched. This would realize the dynamic extraction, real-time computing of pipeline parameters and the corresponding adjustment of pipeline specifications.